Buying less, more often: an evaluation of sachet marketing strategy in an emerging market - Singh, Ramendra (Archīum Ateneo, 2009)
Sachets have for several decades now, been marketed by firms as a strategy to increase trials and market penetration especially in the economically underprivileged societies of the emerging markets. Very often the existence of an economic underclass is assumed to be a necessary prerequisite for the successful implementation of sachet marketing strategy. The article challenges this stance, and through our exhaustive and penetrating analysis of the pervasive and successful use of sachet marketing in an emerging market like India, provides a managerially relevant theoretical framework to evaluate the sachet marketing strategies of firms marketing in India. Our new theoretical framework, grounded in the relevant literature, is also coherent with the recent business practices. We find that sachet marketing strategy does not necessitate the prevalence of poverty, and the critical success factors are an extensive retail distribution, favourable socio-cultural factors, higher perceived value by the consumers, and technology to reduce packaging costs.